Reduction of Food Commodities Contributor Inflation on Household Welfare Changes in The Province of Aceh - Yasrizal Yasrizal; Ishak Hasan; Yusnaidi Yusnaidi (Asosiasi Fakultas Ekonomi dan Bisnis Indonesia, 2017)
The relationship of inflation and poverty can be seen from the contribution of the commodity contributor poverty. Increases in the prices of commodities contributor to poverty led to declining real incomes and loss of income(incomeloss)households, causing poverty. Commodities contributor to poverty is dominated by food commodities. Rice and filter cigarettes are commodities contributor to poverty in Aceh most dominant. Model AIDS is a development of the Engel curve and Marshall equations derived from the theory of maximization of satisfaction. These models use a proportion of household expenditure on a commodity selected to represent variable demand. This research is empirical study. The data used are primary and secondary data obtained from field research and literature. Research will be located in Banda Aceh and Aceh Barat. Using the model of demand is almost ideal or model of AIDS will be seen household behavior in response to changes in commodity prices contributor of poverty. From these observations, the inflation rate of food commodities greatly affect the welfare of the people of Aceh province, both for household Banda Aceh and Meulaboh. Inflation of food commodities had a huge influence to reduce household welfare in Banda Aceh. Furthermore, the majority of households Meulaboh work in agriculture and fisheries. So it can meet its own needs and also be produksen. Many factors substitutes (goods substitution) and cultural factors affecting the level of price elasticity of the goods themselves for food commodities, changes in the elasticity of greater food in Banda Aceh than the district of Meulaboh.Keywords: Elasticity, Food Commodities contributor to poverty, Inflation, Model of AIDS